Diesel Power Generation : Inventories and Black Carbon Emissions in Nigeria - World Bank (World Bank, Washington, DC, 2017)
Diesel gensets contribute to emissions of fine particulate matter (PM), including black carbon, which derives from the incomplete combustion of diesel (as occurs in many diesel generating sets or gensets). Particulate matter is a predisposing factor for respiratory and cardiopulmonary disease leading to increased hospital visits and risk of premature death. Local health costs can have a greater impact in the short-run in densely populated urban centers such as Abuja and Lagos. Black carbon (BC) is the most strongly light-absorbing component of particulate matter and is the second largest warming agent after carbon dioxide. The emerging role of BC as a significant driver of global climate change is increasing attention on its mitigation efforts. In addition to the negative health and the climate effects of emissions, most gensets contribute significantly to noise pollution which further reduces the quality of life of users and non-users alike.